2015
DOI: 10.3390/w7084200
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Principles for Managing the Nexus: Lessons from Historical Global Water Modelling of Central Asia

Abstract: Abstract:The complex relationships within the water-energy-food security nexus tend to be place-specific, increasing the importance of identifying transferable principles to facilitate implementation of a nexus approach. This paper aims to contribute transferable principles by using global model data and concepts to illustrate and analyze the water history of Central Asia. This approach builds on extensive literature about Central Asia and global change as well as recent advances in global water modeling. Deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 76 publications
1
46
0
Order By: Relevance
“…This provides a foundation for an illustrative comparative nexus analysis for three regions centred around selected transboundary Asian river basins. Based on this analysis as well as the relevant findings from the other articles published in this Special Issue [17,21,[26][27][28][29][30][31][32][33], we then discuss what the nexus means in the specific context of transboundary river basins, noting the implications that transboundary context bring to nexus approaches, and vice versa.…”
Section: To Transboundary River Basins Crossingmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a foundation for an illustrative comparative nexus analysis for three regions centred around selected transboundary Asian river basins. Based on this analysis as well as the relevant findings from the other articles published in this Special Issue [17,21,[26][27][28][29][30][31][32][33], we then discuss what the nexus means in the specific context of transboundary river basins, noting the implications that transboundary context bring to nexus approaches, and vice versa.…”
Section: To Transboundary River Basins Crossingmentioning
confidence: 99%
“…As the name suggests, the purpose of the comparative analysis is to provide a general comparison of how the nexus manifests itself in different transboundary regions with large river basins. It builds on our previous research in these regions (e.g., [27,30,[56][57][58][59][60][61][62][63][64][65][66]) as well as key literature referred to in the text. Comparative analysis is not intended to provide an in-depth analysis of a nexus situation in any particular region or river basin.…”
Section: Comparative Nexus Analysis In Three Asian Regions With Largementioning
confidence: 99%
“…The nexus concept, which considers the tradeoffs between different water-dependent activities, has recently received a strong attention for mitigating Central Asia's water challenges. Typically, a strong emphasis is on energy and food, because (a) hydropower plays a significant role for regional energy production and (b) irrigation is the largest single consumer of water (de Strasser et al 2016;Guillaume et al 2015). In fact, a centrally managed water-food-energy nexus existed during socialist times, but collapsed with the breakup of the Soviet Union (Bekchanov and Lamers 2016).…”
Section: Water Usage and Managementmentioning
confidence: 99%
“…On the implementation side, a specific focus has been on holistic concepts such as Integrated Water Resources Management and the food-waterenergy nexus (Guillaume et al 2015;Ibisch et al 2016a;Jalilov et al 2015;Karthe et al 2015b), which lie at the core of most national water management strategies of the region. Advances in water management increasingly require a sound scientific basis, which over the past decade was covered not only by several books and thematic issues in international journals, but also by the emergence of a specific journal focusing on water management in the Central Asian region (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…This complex nexus requires cooperation between countries that share a common past and should work together to build a secure future where resources are concerned. Guillaume et al [136] reviewed the history of transboundary water use in CA using the nexus concept, and concluded that governments, scientists, civil societies and consumers must all play a role in the transformation of the water-energy-food security framework in order for it to be successful. Such a transformation will only be possible through considerable institutional changes and reforms in the region.…”
Section: Implications For Water Resource Research and Management In Cmentioning
confidence: 99%